2015
DOI: 10.1002/bit.25866
|View full text |Cite
|
Sign up to set email alerts
|

Achieving complete nitrogen removal by coupling nitritation‐anammox and methane‐dependent denitrification: A model‐based study

Abstract: The discovery of denitrifying anaerobic methane oxidation (DAMO) processes enables the complete nitrogen removal from wastewater by utilizing the methane produced on site from anaerobic digesters. This model-based study investigated the mechanisms and operational window for efficient nitrogen removal by coupling nitritation-anaerobic ammonium oxidation (Anammox) and methane-dependent denitrification in membrane biofilm reactors (MBfRs). A mathematical model was applied to describe the microbial interactions am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 40 publications
3
21
3
1
Order By: Relevance
“…Chen et al . attempted to resolve this problem by coupling nitritation–anammox and methane‐dependent denitrification, in which denitrifying anaerobic methane oxidation (DAMO) archaea converted nitrate to nitrite . Although Chen et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al . attempted to resolve this problem by coupling nitritation–anammox and methane‐dependent denitrification, in which denitrifying anaerobic methane oxidation (DAMO) archaea converted nitrate to nitrite . Although Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al attempted to resolve this problem by coupling nitritation-anammox and methane-dependent denitrification, in which denitrifying anaerobic methane oxidation (DAMO) archaea converted nitrate to nitrite. 5 Although Chen et al constructed a novel approach to the removal ammonium and methane simultaneously, this process could not bring about phosphorus removal at the same time. Thus, it is necessary to find another effective process to not only reduce nitrate in the effluent of the SNAP process, but also to achieve phosphorus removal simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the potential of 1.2583 V vs. SCE (saturated calomel electrode) could be attributed to oxygen evolution potential, [17][18][19] and the catalytic activity of Ti/RuO 2 -IrO 2 -SnO 2 maintained stability even after cyclic voltammograms tests (50 times). Figure 2 Moreover, the potential of 0.7575 and 1.7906 V vs. SCE can be attributed to the coupled oxidation of ammonia nitrogen and nitrite and oxygen evolution potential, [24][25][26] respectively. Meanwhile, Ti/ RuO 2 -IrO 2 -SnO 2 electrode can generate hydroxyl radicals on their surfaces under a certain potential; the adsorption of hydroxyl ions occurred at the electrodes before the oxygen evolution [27,28]; and ammonium nitrogen could be converted into nitrogen via hydroxyl Table 1.…”
Section: Electrocatalytic Oxidation Of Ammonia Nitrogenmentioning
confidence: 95%
“…Mathematical modeling studies have been conducted to mechanistically understand and ultimately optimize the performance of a CH 4 ‐based MBfR (Chen, Guo, Xie, Yuan, & Ni, ), but they were heavily focused on high‐strength wastewater containing nitrate and ammonium mixtures. This required that the model consider multiple types of active biomass, including AOM‐D archaea, AOM‐D bacteria, and anammox bacteria (Cai et al, , ; Haroon et al, ; Shi et al, ).…”
Section: Introductionmentioning
confidence: 99%